ANALISIS STRATEGI PROMOSI MENURUT EKONOMI ISLAM DALAM MENINGKATKAN VOLUME PENJUALAN - A. A. Miftah; Muthmainnah Muthmainnah; Amala Dinia (CV. Aksara Global Akademia, 2023)
This thesis is entitled Analysis of Promotional Strategies According to Islamic Economics in Increasing Sales Volume (Study of the